2017
DOI: 10.1371/journal.pone.0177626
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community structure transformed after thermophilically composting human waste in Haiti

Abstract: Recycling human waste for beneficial use has been practiced for millennia. Aerobic (thermophilic) composting of sewage sludge has been shown to reduce populations of opportunistically pathogenic bacteria and to inactivate both Ascaris eggs and culturable Escherichia coli in raw waste, but there is still a question about the fate of most fecal bacteria when raw material is composted directly. This study undertook a comprehensive microbial community analysis of composting material at various stages collected ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 78 publications
(107 reference statements)
0
17
0
Order By: Relevance
“…Currently, 32% of the global population rely on sanitation services that are considered less than basic needs, and only 39% of the global population has access to safely managed sanitation services that considers the full life cycle of this organic waste stream (WHO/ UNICEF, 2017). EcoSan via the thermophilic composting of solid organic waste has been shown to be effective at eliminating pathogenic microorganisms (Piceno et al, 2017) and Ascaris, a parasitic nematode that causes intestinal disease (Berendes et al, 2015). It is also thought to be a cost-effective alternative to sewered systems or waste stabilization ponds, particularly in areas of the world where financial resources and infrastructure are limited (WWC, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, 32% of the global population rely on sanitation services that are considered less than basic needs, and only 39% of the global population has access to safely managed sanitation services that considers the full life cycle of this organic waste stream (WHO/ UNICEF, 2017). EcoSan via the thermophilic composting of solid organic waste has been shown to be effective at eliminating pathogenic microorganisms (Piceno et al, 2017) and Ascaris, a parasitic nematode that causes intestinal disease (Berendes et al, 2015). It is also thought to be a cost-effective alternative to sewered systems or waste stabilization ponds, particularly in areas of the world where financial resources and infrastructure are limited (WWC, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Sanergy HSW compost and thermochemically-processed HSW used in our research was fully sterilized. Nevertheless, other studies have described difficulties in sterilizing HSW through thermophilic composting (Niwagaba et al, 2009, Lemunier et al, 2005, Piceno et al, 2017). Lemunier et al (2005) observed Salmonella serovar Enteritidis colonies in mature, thermophilically-composted HSW after 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The buckets are emptied into large composting bins; the walls are made up of pallets filled with carbon-rich material like straw to allow for air to flow through and provide sufficient aeration in the bin. The treatment process has previously been described in Berendes et al [23] and Piceno et al [24]. The bin is sealed when full and left untouched for 2-3 months depending on the temperature and pathogen concentration evolution in the compost bins.…”
Section: Methodsmentioning
confidence: 99%